Older Age is Not a Contraindication for Surgical Treatment of Closed Calcaneal Fractures using the Sinus Tarsi Approach. Issue 4 (November 2022) - Reed, Logan; Mihas, Alexander K.; Andrews, Nicholas A.; Wall, Kevin; Agarwal, Abhinav; Spitler, Clay A.; Johnson, Michael D.
Category: Hindfoot; Trauma Introduction/Purpose: The sinus tarsi (ST) approach for calcaneus fractures has gained popularity in recent years; however, the literature surrounding early complications rates based on age differences for this specific approach is lacking. The objective of this study was to determine if rates of early complications based on age varied for patients undergoing open reduction and internal fixation (ORIF) of calcaneus fractures using the ST approach. Methods: A retrospective review of patients undergoing ORIF for closed calcaneus fractures from 2012 to 2020 was performed. Inclusion criteria was based on an age greater than 18 years old, surgical management of a closed calcaneus fracture using a ST approach, requirement of a preoperative CT scan, and a minimum of 90 days follow-up. Patients were divided into two groups: those under the age of 50 and those over the age of 50. Measurement outcomes included wound dehiscence, superficial surgical site infection, deep infection, and implant removal. Results: A total of 175 patients (186 fractures) were included with 108 patients in the <50 age group and 86 patients in the >50 age group. Mean age was 34.8 and 58.7 years in the younger and older groups, respectively. The older group had similar rates of wound dehiscence (1.3% vs. 1.9%, P=0.761), superficial surgical site infection (1.3% vs. 0.9%, P=0.816), and deep infection (5.1% vs. 4.6%, P=0.876) as compared to the younger group. Eleven (10.2%) fractures in <50 age group required implant removal compared to 13 (16.7%) fractures in the >50 age group (P=0.193). Postoperative Gissane and Bohler angles were not significantly differnet between the two groups. Conclusion: Calcaneal fractures can be debilitating injuries, especially in the older patient population. The present study found that patients with intraarticular calcaneus fractures treated via the ST approach maintain similar early complication rates as compared to younger individuals.